An informed discussion on the impact of COVID-19 and 'enforced' remote working on employee engagement. Issue 2 (15th March 2022) - Pass, Sarah; Ridgway, Maranda
ABSTRACT: COVID-19 has impacted the world at an unimaginable level. National lockdowns were ordered to reduce the virus' spread, resulting in enforced remote working for non-essential workers. Initially considered a short-term situation, working remotely remains the norm for many. While many organizations are keen for the workforce to return to the office, others consider the benefits of remote, or hybrid, working. With remote working becoming the 'new normal' it is vital to consider its impact on employee engagement and the role of HRD in ensuring employees and managers have the skills, knowledge and abilities to engage with the organization, teams and each other. The constant threat of future variants (and other economic and political pressures) means we must learn from our experiences and embed these lessons. We explore these unprecedented changes in employee engagement through an informed discussion by reviewing academic and practitioner literature. Consequently, we offer three propositions reflective of the pandemic and 'enforced' remote working. First, include employees in discussions about the organization's future purpose, with a renewed focus on skills realigned to enhance resilience. Secondly, toffer customized practices that focus on flexibility and inclusivity. Finally, increase employees' autonomy to allow accountablity for their engagement.